Perinatal outcome in uncomplicated pregnancies with oligohydramnios - Gaware, Snehal; Bangal, V. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Oligohydramnios refers to amniotic fluid volume that is less than expected for gestational age. We aimed to assess the perinatal outcomes in pregnancies with oligohydramnios. Methods: The prospective study was conducted in the Department of Obstetrics and Gynecology, Pravara Medical College, Loni in which 200 consecutive singleton pregnancies delivered vaginally, with intact membranes were included. Amniotic fluid index was determined using the Phelan’s technique at the time of admission and women were diagnosed with oligohydramnios if AFI was five or less, which formed the first group and the rest of mother formed the second group. Perinatal outcomes were noted in the proforma as well. Results: Of the 200 mothers included in the study, 38 had AFI ≤ 5. Baseline characteristics was similar in both the groups. Most common antenatal risk factors studies were pregnancy induced hypertension (29% vs 12%; p value <0.05), intrauterine growth restriction (34% vs 10%; p value <0.001) and severe anemia (21% vs 9%; p value <0.05). Proportion of pregnancies needing induction of labor and birth weight less than 2.5 kgs were significantly higher among mothers with oligohydramnios. Conclusions: Authors observed that induction of labor and low birth weight were significantly associated with oligohydramnios. Prospective randomized trials are needed to establish whether early induction of labor in the presence of a oligohydramnios improves perinatal outcome.